2012
DOI: 10.1021/jp305270h
|View full text |Cite
|
Sign up to set email alerts
|

l-Cysteine on Ag(111): A Combined STM and X-ray Spectroscopy Study of Anchorage and Deprotonation

Abstract: Thiols adsorbed on noble metals are prominent model systems for self-assembly and nanotechnology research. l-cysteine is the only proteinogenic amino acid containing a thiol group. A detailed knowledge of the interaction of this molecule with well-defined surfaces is essential to rationalize and advance interfacial amino acid self-assembly and the metal-mediated anchoring of proteins. Here, we address the exemplary system l-cysteine on Ag(111) in UHV, examined by direct STM observations, synchrotron-based XPS,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
70
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(82 citation statements)
references
References 57 publications
12
70
0
Order By: Relevance
“…This might be attributed to either of the following reasons concerning over layer formation: 1) weakening the interaction of L-cysteine with Ag(111) reduces the amount of charge transfer, therefore the strength of the interface dipole can be decreased, 2) change of the adsorption orientation affects the intrinsic dipole moment of cysteine; parallel to the metal surface reduces the intrinsic dipole moment contribution to the interface dipole, and 3) a combination of these two phenomena. Fischer, et al [20] addressed evaporated L-cysteine on Ag(111) and reported that L-cysteine forms a dense-packed layer on Ag(111). In this case, the monolayer coverage is chemosorbed to Ag(111) forming silver-sulfur bonding, and L-cysteine exists mainly as a zwitterion for all the layers.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This might be attributed to either of the following reasons concerning over layer formation: 1) weakening the interaction of L-cysteine with Ag(111) reduces the amount of charge transfer, therefore the strength of the interface dipole can be decreased, 2) change of the adsorption orientation affects the intrinsic dipole moment of cysteine; parallel to the metal surface reduces the intrinsic dipole moment contribution to the interface dipole, and 3) a combination of these two phenomena. Fischer, et al [20] addressed evaporated L-cysteine on Ag(111) and reported that L-cysteine forms a dense-packed layer on Ag(111). In this case, the monolayer coverage is chemosorbed to Ag(111) forming silver-sulfur bonding, and L-cysteine exists mainly as a zwitterion for all the layers.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, an understanding of the interaction of L-cysteine with metal surfaces is necessary. There have been experimental and theoretical research studies that examined the behavior of L-cysteine adsorbed on different faces of gold [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19], silver [20][21][22][23], and copper [24][25][26] metallic single crystals as model systems for understanding the interaction of L-cysteine with metal surfaces and also L-cysteine adsorbed on some other surfaces considering technological interests [27][28][29][30][31][32][33][34][35]. In the experimental studies, the L-cysteine sample for investigation was formed using either the self-assembly or evaporation method.…”
Section: Introductionmentioning
confidence: 99%
“…On the contrary, three different adsorption regimes are identified for Cys/Ag(111) [44]: 1) the multilayer, in which Cys zwitterions physisorb on top of an already present monolayer of molecules and maintain their SH-group intact; 2) the  phase, consisting of a single layer of zwitterionic molecules chemisorbed through their deprotonated S-group; 3) the  phase, produced upon annealing the  phase to T > 393 K and consisting in a mixture of anionic and neutral molecules. While many amino acids adsorb in an anionic form upon deposition [175], thermally activated deprotonation of the ammonium group was previously reported only for Met on Cu(111) [62].…”
Section: Adsorption State Of Aa At Ag Surfacesmentioning
confidence: 95%
“…In addition, the availability of a tunable X-ray source offers the possibility to perform also edge spectroscopies, in particular Near Edge X-ray Absorption Fine Structure (NEXAFS). Providing significant information on the molecular bonds orientation, this technique is very helpful for the characterisation of the structural conformation of the adsorbed molecules [44][45][46].…”
Section: Spectroscopic Techniquesmentioning
confidence: 99%
“…1-3 Thiols adsorption has also been studied on the other coinage metals [4][5][6][7] . Thiols 4,[8][9][10][11][12][13][14][15] , disulfides [16][17][18][19] , methionines [20][21][22][23][24] , cysteines [25][26][27][28][29][30][31][32][33] , etc. have been studied experimentally and theoretically.…”
Section: Introductionmentioning
confidence: 99%